Ibn Malik Position Which It Differed Albesrion and Alkovion | موقف ابن مالك مما اختلف فيه البصريون والكوفيون - Muhammad Syasi (Al-Zahra : Journal for Islamic and Arabic Studies, 2015)
The purpose of this research is to know Ibn Mâlik position toward the different opinion between Albesrion and Alkovion. To answer this problem, the researcher access to Ibn Mâlik ideas and his steps in the controversial treatment. This researh depends on his book Syarh al-Tashîl. Because it has his deep investigation and analysis on grammatical issues. It was noted that he has an attitude and problem solving steps as follows: (1) understand the essence of the issue is controversial, (2) read all the different views in each issue an accurate reading, (3) understand the essence of every opinion on every issue, (4) stated views that improves speech them, (5) critic each of opinion, (6) choose the best opinion of demonstrable base, and (7) report and prove the fixed rule of al-Qaida. These steps are characterized by these characteristics: (1) non-discrimination, (2) criticism and verification, (3) respect, and (4) wise and educative.This analysis concludes that Ibn Mâlik has a cautious attitude, scientific, objective and educative to the differences problem between Basra's school and Kufas school. It mean that Ibn Mâlik was not fanatical to one of them. So his thoughts grammatical resides on an objective and pedagogic basis.